Dielectric loss tangent of dipole rotator in two-pit potential of hindered rotation - Vovchenko, O. E.; Korochkova, T. E.; Rozenbaum, V. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2007)
The azimuthal hopping rotation of the adsorbed polar molecule in double-well potential exposed to the external variable electric field is considered. Analytical expressions for temporal dependence of average dipole moment, frequency dependence of polarizability and average angular velocity are obtained and characterized by stochastic resonance. It is shown that the unidirectional rotation exists only at simultaneous modulation of minima and maxima of potential by the external field. Influence of asymmetry of potential on the spectrum of dielectric losses and other properties of rotation is studied.